2001
DOI: 10.1901/jaba.2001.34-77
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Awareness Enhancement Device for the Treatment of Thumb Sucking in Children

Abstract: An evaluation of the awareness enhancement device (AED) described by Rapp, Miltenberger, and Long (1998) was conducted with 2 children who engaged in thumb sucking past the age at which it was developmentally appropriate. The AED effectively suppressed thumb sucking for both children. Future research evaluating the AED is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 3 publications
2
4
0
Order By: Relevance
“…Furthermore, the bald patches in her hair were hardly visible after the intervention. Consistent with existing research (e.g., Stricker et al, 2001 ; Himle et al, 2018 ), we demonstrated that the use of wearable technology in HRT can be effective also in a naturalistic setting by application of an unobtrusive and user-friendly wearable device to a person suffering from Trichotillomania with comorbidities of examination phobia and ADHD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the bald patches in her hair were hardly visible after the intervention. Consistent with existing research (e.g., Stricker et al, 2001 ; Himle et al, 2018 ), we demonstrated that the use of wearable technology in HRT can be effective also in a naturalistic setting by application of an unobtrusive and user-friendly wearable device to a person suffering from Trichotillomania with comorbidities of examination phobia and ADHD.…”
Section: Discussionsupporting
confidence: 90%
“…Wearable technologies can increase the awareness of BFRBs by warning the individual each time the BFRB occurs (e.g., via vibration alert). According to Stricker et al (2001) two different mechanisms are conceivable: (1) wearable technology leads to increased awareness of the BFRB and thereby reduces it and (2) the frequency of the BFRB is reduced due to alerts of the wearable technology via negative reinforcement. Up to now, the amount of studies examining the application of wearable technologies is still sparse.…”
Section: Introductionmentioning
confidence: 99%
“…of the collar. This device reduced hair pulling in one mentally retarded adult , and thumb sucking in two children (Stricker, Miltenberger, Garlinghouse, Deaver, & Anderson, 2001).…”
Section: Other Forms Of Awareness Trainingmentioning
confidence: 99%
“…Thumb-sucking occurs most frequently when the child is alone. 30 Therefore, a modality that does not require close monitoring of the child may be more successful in treating the habit.…”
Section: Emotional Theorymentioning
confidence: 99%
“…Examples include: the sharp rake, the blunt rake, lingual spurs, the vertical crib, the palatal bar, the horizontal crib, the Graber appliance and the blue grass appliance. While some of these appliances have been described as cruel and inhumane, 30 the palatal crib (vertical crib/tongue crib) has been reported to be successful in treating a thumb sucking habit. [32][33][34][35] The habit may intensify if the child is criticised, nagged or threatened.…”
Section: Emotional Theorymentioning
confidence: 99%